Uzbekistan : Scaling Up Energy Efficiency in Buildings - World Bank Group (World Bank, Washington, DC, 2016)
This study was undertaken by the World Bank to inform the potential areas and means ofassistance to the Government of Uzbekistan in scaling up energy efficiency (EE) investmentsin residential, commercial, and public buildings, focusing on energy use and efficiency inspace heating. Considering the ongoing World Bank assistance in modernizing districtheating services in selected cities in Uzbekistan, this study is explicitly concerned withresidential, commercial, and public buildings that are not served by district heating. The main objective of the study was to identify scalable EE interventions that could be deployed in the next 3 to 5 years. Three specific areas were investigated: (a) a market assessment for upgrading space heating and water heating equipment in detached homes and commercial buildings; (b) an analysis of the issues and options for scaling up investmentin thermal retro fit of public buildings; and (c) a gap analysis on the compliance enforcementof building EE standards in newly constructed housing. The study did not look into thermalretrofit of existing residential buildings, which holds significant energy-saving potential, butalso is among the most complex and challenging of EE interventions. A separate in-depthanalysis would be required to adequately address the issues involved. The three areas of investigation are broadly consistent with the priorities for improving EE in buildings stated in Presidential Decree No. PP-2343: Program of Measures to Increase Energy Efficiency and Introduce Energy-Saving Technologies in the Sectors of Economy andSocial Sphere during 2015–2019. In particular, the presidential decree singled out actions in (a) replacement of nonstandard and inefficient boilers for space-heating and hot watersupply in detached houses; (b) channeling of energy cost savings in state budget-funded organizations toward funding EE investments in these entities; and (c) improvement of rulesand norms for EE requirements for new buildings. The findings and recommendations of the study, summarized below, are intended to inform discussions between the Government and the World Bank on the issues and options to address the main constraints to implementing the priority actions identified in thePresidential Decree No. PP-2343. Detailed courses of action on specific EE interventions inbuildings could then be developed based on the outcomes of these discussions.